The Relationship between the Renewable Energy and CO2 Emissions to the Indonesian Economy - Heru Wahyudi (International Journal of Energy Economics and Policy)
The Indonesian government through the National Energy Council (DEN) has a target for new renewable energy to be increased, starting from 2025 with a target of 23 percent to 2060 with a target of 66 percent, but in fact new renewable energy in Indonesia only increases 0.55 percent per year. Indonesia has great potential, but can the potential be maximized by the government in the direction of a better and environmentally friendly energy policy. This study analyzes the movement of renewable energy and C02 emissions to the Indonesian economy from 1990-2021, using the Vector Error Correction Model (VECM) statistical method by considering short-term and long-term results in the model. The results show that in the long and short term economy the role of GDP per unit of energy use for the economy is needed and has a positive effect, the role of carbon emissions in the short and long term C02 has a positive and significant direction, non-renewable energy in the long term and short term is still moving negative and significant, this indicates that renewable energy in Indonesia tends to be low, energy replacement must be carried out slowly and gradually, shock response conditions conclude when GDP energy use and CO2 are affected by a negative shock will disrupt economic development, meanwhile, if there is a negative shock on consumption Renewable energy still tends to be stable and positive for the development of the Indonesian economy.